Different clinical presentations of choledochal cyst among infants and older children: A 10-year retrospective study. Issue 17 (April 2017) - Badebarin, Davoud; Aslanabadi, Saeid; Teimouri-Dereshki, Amir; Jamshidi, Masoud; Tarverdizadeh, Tuba; Shad, Kaveh; Ghabili, Kamyar; Khajir, Ghazal
Abstract : Abstract: Choledochal cyst is a rare and often benign congenital cystic dilation throughout the biliary tree. Due to the benign nature of choledochal cyst among early-diagnosed patients, the clinical assumption and diagnosis seem to be of utmost significance. Therefore, we sought to assess different clinical manifestations of choledochal cyst and relevant laboratory findings in infants and older children. Retrospectively, medical records of all patients with the diagnosis of choledochal cyst between 2005 and 2015 were reviewed. Demographic data, initial clinical presentation, positive findings on physical examination, history of any remarkable behavior such as persistent and unexplained crying and poor feeding, and diagnostic imaging modalities were listed. In addition, laboratory values for total and direct bilirubin, alkaline phosphatase, alanine transaminase, aspartate transaminase, prothrombin time, and partial thromboplastin time (PTT) were recorded for each patient. Patients were divided into 2 groups; younger than 1-year-old (infants), and 1 year to 18 years old (older children). Demographic data, clinical data, and laboratory values were compared between the infants and older children. Thirty-two patients with a diagnosis of choledochal cyst were included in the study: 9 patients (28.12%) were infants and 23 patients (71.87%) were older children. Abdominal pain was the most common presenting symptom (62.5%), followed by nausea/vomiting (59.4%) and jaundice (28.1%). None of the patients presented with the classic triad of abdominal pain, jaundice, and right upper quadrant mass. Seventeen older children (73.91%) presented with nausea and vomiting, while 2 subjects (22.22%) in the infantile group presented with this feature ( P = .01). Similarly, abdominal pain was found in 20 older children (86.95%); however, none of the infants presented with abdominal pain at diagnosis ( P < .001). By contrast, the abdominal mass was more detected in infants than the older children (33.33% vs. 0%, P = .01). In terms of laboratory values, the median PTT was 44 and 36 s in infants and older children, respectively ( P = .04). Infants were more likely to present with abdominal mass and older children were more likely to have nausea, vomiting, and abdominal pain. Furthermore, infants had more prolonged PTT than older children, implying a potential bleeding tendency.